2017
DOI: 10.1111/jir.12450
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive behaviour, executive function and employment in adults with Down syndrome

Abstract: Background Individuals with Down syndrome (DS) demonstrate difficulties with aspects of executive function (EF) and adaptive behaviour across the lifespan. There is a current lack of information regarding how these difficulties relate to employment outcomes in adulthood. This study evaluated the adaptive behaviour and EF profiles of individuals with DS during early adulthood and the association between these areas of functioning and employment status. Methods Parents or caregivers of primarily young adults wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 51 publications
(135 reference statements)
2
38
1
2
Order By: Relevance
“…It is important to note that the previous studies involved samples of children with ASD and TD. As stated before, research (including this study) has consistently showed that social skills are a relative strength in people with DS, compared to other adaptive and intellectual skills 32,33 , while EF has been reported as a difficulty in people with DS 16,27,64 . Based on this, our hypothesis is that people with DS might tap other abilities to develop their social skills, including understanding and successfully resolving social situations.…”
Section: Discussionsupporting
confidence: 76%
“…It is important to note that the previous studies involved samples of children with ASD and TD. As stated before, research (including this study) has consistently showed that social skills are a relative strength in people with DS, compared to other adaptive and intellectual skills 32,33 , while EF has been reported as a difficulty in people with DS 16,27,64 . Based on this, our hypothesis is that people with DS might tap other abilities to develop their social skills, including understanding and successfully resolving social situations.…”
Section: Discussionsupporting
confidence: 76%
“…[169][170][171][172][173][174] DS is characterized by learning, memory, and language abnormalities that result in mild to moderate intellectual disability. [175][176][177][178][179][180][181][182] Additional neurological hallmarks of DS include motor dysfunction and hypotonia 178,[183][184][185] and predisposition to AD pathology. 178,[186][187][188][189] In recent years, research in DS has been increasingly focused on the degeneration and dementia hallmarks of AD in DS.…”
Section: Modeling Neurological Symptoms and Behavioral Deficitsmentioning
confidence: 99%
“…Ages and scores given as mean (SD; range). NR indicates “not reported”StudyIQ testScore type(s) providedParticipantsParticipant agesRaw scoresStandardised scoresFloor effectsTests not specifically designed for children and adolescents (most recent first) Lao et al, [26]PPVT-IVStandardised score and age-equivalent score5237.3 (6.6; 30–50)NR56.6 (17.2) standardised score; 8.19 (3.44) age-equivalent scoreNR Hartley et al [14]*PPVT-IVAge-equivalent score5837.6 (6.8; ≥ 30)NR8.10 (3.34)NR Tomaszewski et al [15]Stanford Binet 5th EdFull IQ score3125.9 (5.92)NR46.6 (9.1)NR Sinai et al [11]KBIT-2Raw scores for verbal and non-verbal subscales30 no dementia50.9 (4.83)Total, 23.17 (19.50; 3–63);Verbal, 16.37 (13.33; 1–47);Non-verbal, 6.8 (6.92; 0–15)NRVerbal, 0%;Non-verbal, 16.7%19 diagnosed or possible dementia55.6 (6.77)Total, 9.74 (11.06; 1–49);Verbal, 6.53 (7.16; 0–34);Non-verbal, 3.21 (4.16; 0–20)NRVerbal, 5.3%;Non-verbal, 21.1% Startin et al [16]KBIT-2Raw scores for verbal and non-verbal subscales; full IQ scores floor effects only130 aged 36+ years without dementia47.77 (7.01; 36–71)Verbal, 30.55 (17.47; 2–80);Non-verbal, 12.55 (6.57; 0–32);NRVerbal raw, 0%;Verbal IQ, 66.7%;Non-verbal raw, 6.7%;Non-verbal IQ, 39.4%51 aged 36+ years with dementia54.20 (6.95; 38–67)Verbal, 18.68 (13.77; 1–51);Non-verbal, 8.29 (6.45; 0–19)NRVerbal raw, 0%;Verbal IQ, 84.0%;Non-verbal raw, 16.7%;Non-verbal IQ, 62.5%124 aged 16–35 years25.24 (5.53; 16–35)Verbal, 35.03 (16.77; 2–82);Non-verbal, 14.98 (6.9; 0–32)NRVerbal raw, 0%;Verbal IQ, 50.8%;Non-verbal raw, 4.1%;Non-verbal IQ, 33.9% de Sola et al [17]KBIT (Spanish version)Full IQ score; combined verbal and non-verbal standardised KBIT score8623.3 (4.3; 16–34)NRFull IQ median, 41;Standardised KBIT score, 105 (17.8; 80–180)41.9% Ghezzo et al [8]WAIS-RFull IQ score; verbal IQ score; performance IQ score36 adults with DS (of a larger sam...…”
Section: Iq and General Ability Tests In People With Dsmentioning
confidence: 99%